Dogsong - Paulsen, Gary (New York Scholastic, 1990)
A fourteen-year-old Eskimo boy who feels assailed by the modernity of his life takes a 1400-mile journey by dog sled across ice, tundra, and mountains seeking his own "song" of himself.
Keywords: Eskimos -- Juvenile fiction